Families with neurocutaneous syndromea - Report of two cases - Saha, Radheshyam; Mahmud, Reaz; Hossain, Mohammad Zaid; Sarkar, Prodip Kumar (Journal of Dhaka Medical College, 2013)
Corrigendum The Article "Families with neurocutaneous syndromea - Report of two Cases" was published in JDMC Vol.22(1) in April 2013. The name of one of the authors was written 'Prodip Kumar Sarker', which is to be read as 'Prodip Kumar Sarkar'. (4th August 2014) Neurocutaneus syndrome is inherited as autosomal dominant condition.Tuberous sclerosis is one of the important neurocutaneous disorder characterized by development of widespread hamartomatous lesions involving skin, brain, kidney, retina etc. Recently we came across two cases of tuberous sclerosis. Both cases presented with status epilepticus and had a positive family history but the first case also had family history of neurofibromatosis. DOI: http://dx.doi.org/10.3329/jdmc.v22i1.15709 J Dhaka Medical College, Vol. 22, No. 1, April, 2013, Page 102-107